18 18F-flouride pet MR in valvular and coronary heart disease; a pilot investigational study. (May 2018) - Andrews, Jack; Moss, Alastair; Doris, Mhairi; Pawade, Tania; Adamson, Philip; MacNaught, Gillian; Lucatelli, Christophe; Newby, David; Dweck, Marc
Abstract : Introduction: Recently, PET-MR has emerged as a novel imaging technique capable of assessing myocardial disease, inflammation and microcalcification. We aimed to investigate aortic valve and coronary 18F-NaF activity in subjects with aortic stenosis (AS) and coronary disease. Methods: 25 patients underwent 18F-NaF PET-MR scanning. PET data was acquired in list mode with a standard Dixon attenuation correction technique. MR angiography was performed following infusion of Gadolinium. PET activity was quantified by calculating standardised uptake values (SUV) and tissue to background ratios (TBR) on fused PET-MR images. Culprit arteries were identified during preceding invasive coronary angiography. Results: 22 of 25 patients completed the protocol. Patients with aortic stenosis had higher aortic valve SUVmax and TBRmax (Valve SUV max/left atrial SUV mean) than those without (SUVmax 1.89±0.60 vs 1.15±0.38, p=0.001 and TBRmax 2.87±0.98 vs 1.77±0.43, p=0.001). 13/13 patients with MI had focal 18F-NaF uptake in the culprit vessel with an SUV max and TBR max greater than the proximal referent vessel (SUV max 1.05±0.26 vs 0.74±0.13, p=0.002 and TBRmax 1.64±0.47 vs 1.16±0.26, p=0.004). Conclusion: Similar to previous 18F-NaF PET CT studies, 18F-NaF PET-MR uptake is significantly greater in those with confirmed AS than those without. 18F-NaF uptake also accurately identifies culprit arteries in those with recent MI. The results share similarities with recently published valvular and coronary 18F-NaF PET-CT studies and thus promote further research into the utility of cardiovascular PET-MR as a complementary hybrid imaging technique.